The macrostructure of the newspaper front page – a Polish-Czech-Slovak comparative approach - Sojda, Sylwia; Ślawska, Magdalena (Papers in Linguistics, 2025)
The article is an attempt at a comparative analysis of the front pages of Polish, Czech, and Slovak newspapers that presented the November 2024 US presidential election. Importantly, it compares textual spaces created under similar geopolitical conditions and in closely related language systems. 42 first pages were analysed and treated as macrostructures. The study identified different strategies of informing about the same event resulting from, for example, different composition schemes. The article analyses different elements in depicting the presidential election on the first pages of national dailies in Poland, Czechia, and Slovakia.